2020
DOI: 10.1177/1759720x20966123
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid pain in axial spondyloarthritis, including fibromyalgia

Abstract: The main symptom in patients with axial spondyloarthritis (axSpA) is inflammatory back pain, caused principally by inflammation of the sacroiliac joints and the spine. However, not all back pain in patients with axSpA is related to active inflammation: other types of pain can occur in these patients, and may be related to structural damage (e.g. ankylosis), degenerative changes, vertebral fractures or comorbid fibromyalgia, which are not uncommon in these patients. Structural damage and ankylosis may lead to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“… 5 7 Widespread pain can be misdiagnosed as fibromyalgia, which is prevalent in patients with axSpA, and can mimic entheseal pain. 8 The results from the Corrona Psoriatic Arthritis (PsA)/SpA registry including 498 patients with axSpA (307 (61.6%) men and 191 (38.4%) women) underline the need of improving the awareness of sex differences in the presentation of axSpA. 5 Authors revealed that the patient journey to diagnosis of axSpA is much longer and more arduous in women, as measured by clinical assessment and in patient-reported outcomes (PROs): women had higher disease activity as measured by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index and physician global assessment and had higher tender/swollen joint counts and enthesitis scores.…”
Section: Introductionmentioning
confidence: 99%
“… 5 7 Widespread pain can be misdiagnosed as fibromyalgia, which is prevalent in patients with axSpA, and can mimic entheseal pain. 8 The results from the Corrona Psoriatic Arthritis (PsA)/SpA registry including 498 patients with axSpA (307 (61.6%) men and 191 (38.4%) women) underline the need of improving the awareness of sex differences in the presentation of axSpA. 5 Authors revealed that the patient journey to diagnosis of axSpA is much longer and more arduous in women, as measured by clinical assessment and in patient-reported outcomes (PROs): women had higher disease activity as measured by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index and physician global assessment and had higher tender/swollen joint counts and enthesitis scores.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the evaluation of disease activity, the experts underlined the challenges posed by the coexistence of fibromyalgia [36][37][38] or residual pain/disease [39]. This combination creates diagnostic dilemmas and increases the disease activity scores, potentially resulting in over-treatment.…”
Section: 22mentioning
confidence: 99%
“…Вважається, що близько 50% пацієнтів з АС мають хоча б один коморбідний стан, а близько 9% пацієнтів страждають на 3 та більше супутніх захворювання [28,31]. Значущою проблемою у хворих на АС є коморбідність з ФМ, яка характеризується високою поширеністю, складністю діагностики та лікування [16,27].…”
Section: вступunclassified